Conversion Painful Ankle Arthrodesis to Total Ankle Arthroplasty: Case Series and Literature Reviews - Jen-Hung Chen MD (Foot & Ankle Orthopaedics)
Category: Ankle Arthritis; Hindfoot Introduction/Purpose: Pain following an ankle arthrodesis continues to be a challenging problem. Degenerative changes in the adjacent joints also have been reported by several authors. Extending the fusion to the hindfoot may increase the nonunion rate and, hence, undermine the results of the procedure, while limiting function. Given the complexity of this clinical situation, conversion total ankle arthroplasty (TAA) has arisen as a valid treatment choice. Methods: From 2018 to 2023, twelve total ankle arthroplasties with Inbone II (Wright Medical Technology, Arlington, Tennessee) were performed in patients who had undergone a prior ankle arthrodesis. Five of them were nonunion of previous ankle arthrodesis and seven of them were due to adjacent hindfoot arthritis. The mean period of ankle arthrodesis status was 18.5 years (range, 1 to 26). The mean age was 63.7 years old (range, 55 to 77). The preoperative ankle joint weight-bearing plain films, lower limbs split scanography and CT were obtained. Due to hindfoot adjacent arthritis following previous ankle arthrodesis, concomitant subtalar arthrodesis was performed in all three patients and talonavicular arthrodesis was performed in two patients. Immediate weight bearing ambulation with protection was allowed postoperatively. The mean follow-up duration was 42.6 months (range, 8 to 65). Results: The mean visual analog scale pain score improved from 75 preoperatively to 10 at the latest follow up. The mean AOFAS hindfoot score increase from 32.5 to 76. The mean range of motion of ankle joints from 5.2 degree (range, 0~10) to 37.5 degree (range, 20~50). Eleven patients were satisfied with the results, but one were still unsatisfied. Preoperative pain improved much more about 6 weeks postoperatively and gait improved about 3 months postoperatively. No complications including infection, wound poor healing, or early prosthesis failure were found during follow-up. Conclusion: Ankle arthrodesis takedown with conversion to TAA has been proposed to patients with pain related to an ankle arthrodesis in an effort to improved functional outcomes. Short-term follow-up after conversion of ankle arthrodesis to TAA demonstrated pain relief and improved function in a majority of patients. The rate of complications, particularly talar component settling and migration, is cause for concern. By means of takedown ankle arthrodesis to TAA and arthrodesis of the hindfoot adjacent arthritic joints simultaneously, the ankle joint movement was regained and hindfoot pain was relieved. Long-term follow up is still needed.